Evaluation of Vehicle Transportation on KMP. Gambolo and KMP. Ambu – Ambu Operating in the Old Port of Pejat, West Sumatra Province - Kartini, Sri; Sari, Vita Permata; Sari, Dewi Kartika; Maharani, Raden Ayu Anggita (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
Tua Pejat Port is a Ferry Port in Mentawai Regency, West Sumatra Province that serves the Tua Pejat-Padang route. The Tua Pejat Ferry Port is very important in supporting economic development in Mentawai Regency. On the Tua Pejat-Padang ferry, there are still vehicles that enter the ship without knowing the weight of the vehicle load, the distance between adjacent vehicles, the placement of vehicles across, and vehicle tying that is not in accordance with the rules. The type of research used is mixed research with the methodgap analysisas a comparison between existing conditions and expected conditions and as an analysis method used in evaluations that focus on the current gap with the targeted conditions. Data analysis by comparing the existing conditions of vehicle transportation in the field with vehicle transportation procedures in accordance with applicable regulations. Based on the research results, it can be concluded that the condition of vehicle transportation on the Tua Pejat - Padang ferry at the Tua Pejat Ferry Port is not in accordance with the vehicle transportation procedures that have been regulated in the Regulation of the Minister of Transportation Number 115 of 2016 and the Regulation of the Minister of Transportation Number 30 of 2016. Therefore, port and ship operators must pay more attention to vehicle transportation on ships on the Tua Pejat - Padang route for the safety and security of ships during the voyage.